2016
DOI: 10.1016/j.joms.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Serum Markers of Bone Turnover and Angiogenesis in Patients With Bisphosphonate-Related Osteonecrosis of the Jaw After Discontinuation of Long-Term Intravenous Bisphosphonate Therapy

Abstract: Purpose To analyze serum markers of bone turnover, angiogenesis, endocrine function, and inflammation in bisphosphonate-related osteonecrosis of the jaw (BRONJ) patients who discontinued long-term intravenous bisphosphonate (BP) therapy. Patients and Methods Serum samples were obtained from 25 BRONJ patients who had discontinued long-term intravenous BP therapy for an average of 11.4±8.7 months and 48 non-BRONJ controls who continued receiving intravenous BP therapy. Samples were analyzed for total alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
(65 reference statements)
0
20
0
1
Order By: Relevance
“…After the discontinuation of bisphosphonates, the drug action persists for some years with a slower decrease in bone mineral density (BMD) (Boonen et al , ). Recently, Thumbigere‐Math et al () concluded that the prolonged skeletal half‐life of bisphosphonates may suppress bone turnover markers in BRONJ patients for several years after the discontinuation of intravenous bisphosphonate therapy, suggesting an extended effect on bone homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…After the discontinuation of bisphosphonates, the drug action persists for some years with a slower decrease in bone mineral density (BMD) (Boonen et al , ). Recently, Thumbigere‐Math et al () concluded that the prolonged skeletal half‐life of bisphosphonates may suppress bone turnover markers in BRONJ patients for several years after the discontinuation of intravenous bisphosphonate therapy, suggesting an extended effect on bone homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The search for alternative dose regimens has either been part of attempts to improve adherence to BPs or it has been spurred by the fear of serious side effects of BPs such as osteonecrosis of the jaw (ONJ) and atypical femur fractures (AFFs), the incidence of which seems to be related to long‐term use of relatively high doses. Several studies have explored the potential use of BTMs in predicting which patients might be at risk for these side effects . Unfortunately, most of these studies into the relationships between BTM levels and serious side effects have been characterized by suboptimal study designs and we therefore still do not know if BTMs are useful or not, although it seems unlikely.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Levels of 100–150 pg/ml indicate a moderate risk of BRONJ, while levels of less than 100 pg/ml a high risk (Marx et al, ). Although some studies have validated their applicability (Thumbigere‐Math et al, ), different clinical and preclinical assays and systematic reviews have questioned the use of this biomarker and concluded that its serum level is not a definitive risk predictor for BRONJ (Enciso et al, ; Khan et al, ; Ruggiero & Dodson, ). NTX, the terminal amino fragment of type I collagen which cross‐links with pyridinoline, is a more sensitive marker than CTX and is excreted in the urine following degradation of the bone matrix (Kolokythas et al, ).…”
Section: Skeleton Side Effects Of N‐bps Prevention and Managementmentioning
confidence: 99%
“…Parathyroid hormone (PTH) indirectly promotes bone resorption by osteoclasts and is considered to be an unspecific marker for bone resorption (Kolokythas et al, ). Other biomarkers include proteins involved in bone formation regulation such as under‐carboxylated osteocalcin (Glu‐OC) (Khan et al, ; Thumbigere‐Math et al, ), bone‐specific alkaline phosphatase (BAP) (Khan et al, ; Kolokythas et al, ; Thumbigere‐Math et al, ), salivary proteins such as metalloproteinase‐9–a proteolytic enzyme involved in wound healing mainly expressed by osteoclasts – and desmoplakin – a component of desmosome structures in different cells (Thumbigere‐Math et al, ). Nevertheless, none of them has been related specifically to BRONJ and their role in this pathology requires further research (Thumbigere‐Math et al, ).…”
Section: Skeleton Side Effects Of N‐bps Prevention and Managementmentioning
confidence: 99%